Can radiological assessment of abdominal computerized scans diagnose encapsulating peritoneal sclerosis in long‐term peritoneal dialysis patients?. Issue 1 (January 2017) - Stuart, Sam; Stott, David; Goode, Antony; Cash, Charlotte J; Davenport, Andrew
Abstract: Aim: Encapsulating peritoneal sclerosis (EPS) is a rare but potentially devastating complication of long‐term peritoneal dialysis (PD). Changes to the peritoneal membrane occur with duration of PD therapy. To determine the potential effect of prospective computerized tomography (CT) scanning, we reviewed the scans of patients who had developed EPS compared with those without EPS. Methods: We retrospectively compared CT scans that had been prospectively performed in a screening program for PD patients after 4 years of PD and compared scans from 18 patients with confirmed EPS and 26 vintage matched controls without EPS. Anonymized scans were reported independently by two blinded experienced radiologists. Results: Peritoneal thickening, calcification, bowel tethering, thickening and dilatation were significantly more commonly reported in the EPS group. Total combined radiological scores, also including septation within peritoneal fluid, were significantly higher in the EPS group and the greatest for those who died as a consequence of EPS. Simplified scoring based on presence or absence, then for a score of ≥3.0, gave a receiver operating characteristic value of 0.87 for EPS, with a sensitivity of 78% and specificity of 85%, respectively. Inter‐observer agreement varied from poor to good, being the greatest for calcification and bowel dilatation and the lowest for peritoneal thickening. Conclusion: CT scan reporting can differentiate EPS from peritoneal changes associated with duration of PD therapy. Severity of abnormalities was associated with clinical outcomes. However, inter‐observer agreement varies with different radiological appearances, and future studies are required to determine weighting of radiological changes to provide prognostic information for clinicians and patients. Summary at a Glance: Encapsulating peritoneal sclerosis is a dreaded outcome in PD. This study examines whether serial CT scans can predict those at risk and attempts to derive a CT based score for predicting EPS.